Shelter dogs as indicators for Trypanosoma cruzi infection in an urban area of Aracaju, Brazil - Cruz, Ana Carla F.G.; Santos, Natália A.F.; Jeraldo, Veronica de Lourdes S.; Madi, Rubens R.; Rosa, João Aristeu da [UNESP]; Melo, Cláudia Moura de (Elsevier, 2020)
Shelters are places that receive certain species of domestic animals, mostly dogs and cats, that are normally abandoned. These animals are easy to handle because they are crowded and have limited movement. Dogs, due to the close relationship with humans, are considered the main domestic reservoirs in the peridomiciliary cycle of American trypanosomiasis infection in humans. Therefore, in several countries studies are carried out to assess the occurrence of infection in these animals. This work evaluated the occurrence of Trypanosoma cruzi in dogs from shelters in the city of Aracaju, Sergipe. This was an observational and cross-sectional study to detect the occurrence of T. cruzi in blood samples from shelter dogs using polymerase chain reaction (PCR) with the TcZ1/TcZ2 primers. A total of 168 blood samples from dogs (104 females and 64 males) were collected and subjected to DNA and PCR extraction, and seventeen (10.1%) samples showed amplification of the product of the expected size. The TcZ1/TcZ2 primer pair used is considered specific for T. cruzi, and it is capable of amplifying all strains without amplifying other Trypanosoma species. The shelters evaluated had different physical infrastructure; animals positive for T. cruzi were found in all of them, as confirmed by sequencing. It is concluded that shelter dogs, as well as other domestic animals, can function as indicators of the occurrence of T. cruzi in Aracaju-SE, providing relevant epidemiological information for health surveillance and monitoring of Trypanosomatid infections.
Keywords: Chagas Disease; Disease reservoirs; Indicators; Trypanosoma cruzi